Surds and Indices
- Solve the below equation and find the value of ?.
√(13)4 = ?
-
View Hint View Answer Discuss in Forum
? = √(13)4 = √13 x 13 x 13 x 13
Apply the rule of square root.Correct Option: B
? = √(13)4 = √13 x 13 x 13 x 13
Apply the rule of square root.
= 13 x 13 = 169
- 1/1 + xb - a + xc - a + 1/1 + xa-b + xc - b + 1/1 + xb - c+ xa - c = ?
-
View Hint View Answer Discuss in Forum
? = 1/ ( 1 + xb - a + xc - a ) + 1/ ( 1 + xa - b + xc - b ) + 1 / ( 1 + xb - c + xa - c )
Apply the law of algebra and solve the given equation.
⇒ ? =1/ ( 1 + xb/xa + xc/xa ) + 1/ ( 1+ xa/xb + xc/xb ) + 1/ ( 1 + xb/xc + xa/xc )Correct Option: B
? = 1/ ( 1 + xb - a + xc - a ) + 1/ ( 1 + xa - b + xc - b ) + 1 / ( 1 + xb - c + xa - c )
Apply the law of algebra and solve the given equation.
⇒ ? =1/ ( 1 + xb/xa + xc/xa ) + 1/ ( 1+ xa/xb + xc/xb ) + 1/ ( 1 + xb/xc + xa/xc )
⇒ ? = xa/ ( xa+xb+xc ) + xb/ ( xb + xa+ xc ) + xc/ ( xc+xb+xa )
⇒ ? = ( xa + xb + xc ) / ( xa + xb + xc ) = 1
- If a = √3/2, then √1 + a + √1 - a =?
-
View Hint View Answer Discuss in Forum
Let us assume
P = √1 + a + √1 - a
Square on both side and put the value of a in solved equation.Correct Option: D
Let us assume
P = √1 + a + √1 - a
Square on both side,
P 2 = ( √1 + a + √1 - a ) 2
Use the formula ( a + b ) 2 = a 2 + b 2 + 2ab
we will get
⇒ P 2 = (1 + a) + (1- a) + 2 √1 + a x √1 - a
⇒ P 2 = (1 + a) + (1- a) + 2 √(1 + a ) x ( 1 - a )
⇒ P 2 = 2 + 2 √1 - a2
⇒ P 2 = 2 (1 + √1 - a2)
Now put the value of a which is given in question;
⇒ P 2 = 2 (1 + √1 - ( √3/2 )2)
⇒ P 2 = 2(1 + √1 - 3/4 )
⇒ P 2 = 2(1 + √1/4 )
⇒ P 2 = 2(1 + 1/2) = 2 x 3/2 = 3
⇒ P= √3
∴ (√1 + a + √1 - a) = √3
- If (p/q)n - 1 = (q/p)n - 3, then the value of n is
-
View Hint View Answer Discuss in Forum
Given equation is below
(p/q)n - 1 = (q/p)n - 3
Apply the law of Fractional Exponents and Laws of Exponents
a - m = 1/a m
or
am = 1/a - m
and
if pX = pY then X will be equal to Y. means X = Y;Correct Option: D
Given equation is below
(p/q)n - 1 = (q/p)n - 3
Apply the law of Fractional Exponents and Laws of Exponents
a - m = 1/a m
or
am = 1/a - m
(p/q)n - 1 = (q) - (n - 3) x 1/ (p) - (n - 3)
(p/q)n - 1 = (p) 3 - n x 1/ (q) 3 - n
(p/q)n - 1 = (p/q) 3 - n
if pX = pY then X will be equal to Y. means X = Y;
⇒ n - 1 = 3 - n
⇒ 2n = 4
⇒ n = 2
- If (1/5 )3a = 0.008 Find the value of ( 0.25)a
-
View Hint View Answer Discuss in Forum
(1/5 )3a = 0.008 = 8/1000 = 1/125 = (1/5 )3
Apply the Algebra Law and Solve the equation.Correct Option: C
(1/5 )3a = 0.008 = 8/1000 = 1/125 = (1/5 )3
Apply the Algebra Law and Solve the equation.
⇒ 3a = 3
∴ a = 1
∴ ( 0.25 )a = ( 0.25 )1 = 0.25